Clinical Characteristics, Comorbidities, and Sex-related Differences Among Smoking and Non-smoking Patients with Rheumatoid Arthritis: A Matched Case–control Study - Hanan M. Fathi; Samar Tharwat; Khaled El Hadidi; Yousra H. Abdel-Fattah; Marwa A. Amer; Amira M. Ibrahim; Saad M. Elzokm; Hanan M. El-Saadany; Shereen Elwan; Doaa Mosad; Samah Ismail Nasef; Maha E. Ibrahim; et al. (Saudi Journal of Medicine and Medical Sciences)
Background: Smoking may increase levels of pro-inflammatory cytokines, which is an important contributor to rheumatoid arthritis (RA) pathogenesis. Objectives: The aim of this study was to describe the characteristics of RA patients who were smokers compared with non-smokers. Methods: A total of 849 RA patients who were smokers out of a large RA cohort of 10,364 patients (8.2%) were compared to 924 age-, sex-, and body mass index-matched RA patients who were non-smokers. Patients were subjected to full history-taking and clinical examination. Laboratory tests such as rheumatoid factor (RF) and anti-cyclic citrullinated peptide (anti-CCP) were measured. The disease activity score 28 (DAS28) and the health assessment questionnaire (HAQ) score were assessed. Results: The mean age among smokers was 46.4 ± 11.3 years, the male–female ratio was 3:1, and the mean disease duration was 6.4 ± 6.2 years. There was a significantly higher frequency of diabetes mellitus, hypertension, and metabolic syndrome in smokers compared to non-smokers (13.7%, 17.1%, and 9.2% vs. 8.4%, 12.9%, and 3.5%; P < 0.0001, P = 0.01, P < 0.0001, respectively), while hypothyroidism was more common in non-smokers (P = 0.03). Rheumatoid nodules (P = 0.03), oral ulcers (P = 0.002), keratoconjunctivitis sicca (P = 0.043), and neurological manifestations (P = 0.002) were significantly more common in smokers, but the DAS28 was lower (4.2 ± 1.5 vs. 4.8 ± 2.5; P < 0.0001). RA-related changes were significantly more common in female smokers than in males. On regression analysis, none of the differences found in the comparison between smokers and non-smokers remained significant. Conclusions: Smoking in RA patients was found to be associated with a higher frequency of traditional comorbidities, rheumatoid nodules, oral ulcers, sicca complex, and neurological manifestations, but a lower disease activity. There is an obvious sex-driven pattern, with clinical alterations occurring more frequently in female smokers. Higher RF, anti-CCP, and double seropositivity are more observable in males and positive antinuclear antibody in females.